MEMBER REGISTRATION SYSTEM STATE IN SUB Cooperation EMPLOYEES GEDE dari MICROSOFT ACCESS COTTAGE 1997 - Panca Indria Kusuma; Rahayu Noveandi, Skom, MM (Jurnal Sistem Informasi, 2007)
In scientific writing, the writer explains the design Member Registration System atthe District Cooperative Servants Pondok Gede using Microsoft Access.